KEBUGARAN JASMANI PADA LANJUT USIA - Dwi Purwantini (JURNAL KESEHATAN MERCUSUAR, 2021)
Physical fitness is ability to carry out daily activities safely and effectively without experiencing significant fatique, and stikk having energy left to caary out leisure and recreational activities. The purpose of this study was determinethe description of physical fitness in the elderly. Research design with descriptive studied. The subjects of this study were elderly aged 60 year old in RW III Kelurahan Kebraon, Karang Pilang as many as 36 respondens. The sampling technique was purposive sampling. The data collected during the research were characteristic was gender, age, nutrisional status, physical activity, time physical activity and length of sitting. Sample characteristic data was colleted by filling out questionnaires and physical fitness was collected bay 2 minutes step test. Research data shows that 58,3% have good physical fitness and 41,7 have poor physical fitness. The conclution from the study of elderly in RW III, kelurahan Kebraon, Karang Pilang, most of them have good physical fitness. Recommedation from this study were the importance of manintaining physical fitness who are still less fit, especially in the current pandemic condition by continuing to do physical activity to the dose